Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Stress-testing road network resilience using counterfactual flood events (1953–2024) in Great Britain - Yue Li; Raghav Pant; Tom Russell; Fred Thomas; Jim W. Hall; Philip Oldham; Rob Lamb; Paul J. Young (Transportation Research Part D: Transport and Environment, 2026)

Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Distal cryptotephra records in the Falkland Islands refine South American tephrochronology - Panayiotis Panaretos; Alistair J. Monteath; Zoë A. Thomas; Paul G. Albert; Britta J.L. Jensen; James Tamhane; Shaun Woudstra; Gwydion Jones; Rob Scaife; Michael J. Bentley (Quaternary Science Reviews, 2025)

Evaluating the lifetime cumulative dose as a basis for carcinogenic potency of nitrosamines – a key tenet underpinning less-than-lifetime approaches for establishing acceptable intake limits - Susan P. Felter; Ashley M. Mudd; David J. Ponting; Rob Thomas; Alisa Vespa; Timothy J. McGovern; Andreas Zeller; Roland Froetschl; Bodo Haas; Yi Yang; Anthony Lynch; Angela White; et al. (Regulatory Toxicology and Pharmacology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Migratory Birds Advance Spring Arrival and Egg‐Laying in the Arctic, Mostly by Travelling Faster - Thomas K. Lameris; Michiel P. Boom; Rascha J. M. Nuijten; Nelleke H. Buitendijk; Götz Eichhorn; Bruno J. Ens; Klaus‐Michael Exo; Petr M. Glazov; Sveinn Are Hanssen; Philip Hunke; Henk P. van der Jeugd; Margje E. de Jong; et al. (Global Change Biology, 2025)
In the current warming climate, many organisms in seasonal environments advance their timing of reproduction to benefit from resource peaks earlier in spring. For migrants, the potential to advance reproduction may be constrained by their migration strategies, notably their ability to advance arrival at the breeding grounds. Recent studies show various changes in migration strategies, including wintering closer to the breeding grounds, earlier departure from the wintering grounds or faster travels by spending less time at stopover sites. However, whether such changes lead to earlier arrival or earlier breeding remains an open question. We studied changes in migration and reproduction timing in 12 populations of nine migratory birds, including seabirds, shorebirds, birds of prey and waterfowl breeding at Arctic sites bordering the Greenland and Barents Sea, a region undergoing rapid climate warming. The timing of migration and reproduction was derived from tracking and field data and analysed to study (1) how timing has changed in response to the changing moment of snowmelt at the breeding grounds and (2) what adjustments in migration strategies this involved. We found that in years with early snowmelt, egg‐laying in multiple populations advanced, but only two waterfowl populations also advanced arrival in the Arctic. In contrast, arrival in the Arctic generally advanced with time, even when snowmelt or egg‐laying dates did not advance. Earlier arrival with time was mostly explained by populations traveling to the Arctic faster, likely spending less time at stopover sites. Inability to forecast conditions in the Arctic may limit birds to adjust migration timing to annually varying snowmelt, but we show that several species, particularly waterfowl, are able to travel faster and advance the timing of migration over the years. The question remains whether this reflects adaptations to Arctic climate change or other factors, for example, environmental changes along the migratory route.

Advancing Patient Advocacy in Mycology: Cultivating Collaboration in Education, Research, and Policy - Rob Purdie; Rasha Kuran; Ana Alastruey-Izquierdo; Hatim Sati; Juan Luis Rodriguez-Tudela; Martin Hoenigl; John Perfect; Rita Oladele; Thomas J. Walsh; Tom Chiller (Mycopathologia, 2025)
In the healthcare landscape, diseases such as cancer and HIV/AIDS have benefited from the patient's perspective. For fungal diseases, the patient voice remains absent in critical areas such as policy formulation, funding decisions, and research priorities. Patients affected by fungal disease, along with their caregivers and advocacy groups, possess invaluable insights into the challenges and unmet needs they face. By elevating their voices and experiences, policymakers, funding agencies, and researchers can gain a more comprehensive understanding of the multifaceted nature of fungal disease and the urgency of addressing them. This paper addresses the pressing need for a coordinated effort to elevate the patient voice in advocating for improved policies, increased funding, and enhanced research initiatives regarding fungal disease.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

AVOTREX : A Global Dataset of Extinct Birds and Their Traits - Ferran Sayol; Joseph P. Wayman; Paul Dufour; Thomas E. Martin; Julian P. Hume; Maria Wagner Jørgensen; Natàlia Martínez‐Rubio; Ariadna Sanglas; Filipa C. Soares; Rob Cooke; Chase D. Mendenhall; Jay R. Margolis; et al. (Global Ecology and Biogeography, 2024)
Motivation Human activities have been reshaping the natural world for tens of thousands of years, leading to the extinction of hundreds of bird species. Past research has provided evidence of extinction selectivity towards certain groups of species, but trait information is lacking for the majority of clades, especially for prehistoric extinctions identified only through subfossil remains. This incomplete knowledge potentially obscures the structure of natural communities, undermining our ability to infer changes in biodiversity across space and time, including trends in functional and phylogenetic diversity. Biases in currently available trait data also limit our ability to identify drivers and processes of extinction. Here we present AVOTREX, an open‐access database of species traits for all birds known to have gone extinct in the last 130,000 years. This database provides detailed morphological information for 610 extinct species, along with a pipeline to build phylogenetic trees that include these extinct species. Main Types of Variables Contained For each extinct bird species, we provide information on the taxonomy, geographic location, and period of extinction. We also present data on island endemicity, flight ability, and body mass, as well as standard measurements of external (matching the AVONET database of extant birds) and skeletal morphology from museum specimens where available. To ensure comprehensive morphological data coverage, we estimate all missing morphological measurements using a data imputation technique based on machine learning. Finally, we provide an R package to graft all extinct species onto a global phylogeny of extant species (BirdTree). Spatial Location and Grain Global. Time Period and Grain All known globally extinct bird species from 130,000 years ago up until 2024. Major Taxa and Level of Measurement Birds (Class Aves), species level. Software Format Spreadsheets (.csv) stored in Dryad.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Exposure to per- and polyfluoroalkyl substances and alterations in plasma microRNA profiles in children - Yijie Li; Brittney O. Baumert; Nikos Stratakis; Jesse A. Goodrich; Haotian Wu; Shelley H. Liu; Hongxu Wang; Emily Beglarian; Scott M. Bartell; Sandrah Proctor Eckel; Douglas Walker; Damaskini Valvi; et al. (Environmental Research, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Emerging outsource agricultural services enable farmer adaptation in agrifood value chains: A product cycle perspective - Thomas Reardon; Titus Awokuse; Ben Belton; Lenis Saweda O. Liverpool-Tasie; Bart Minten; Genevieve Nguyen; Sara Qanti; Johan Swinnen; Rob Vos; David Zilberman (Food Policy, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Diurnal to interannual variability in the Northeast Atlantic from hydrographic transects and fixed time-series across the Rockall Trough - Eoghan Daly; Glenn Nolan; Alan Berry; Janina V. Büscher; Rachel R. Cave; Levke Caesar; Margot Cronin; Sheena Fennell; Kieran Lyons; Aedín McAleer; Gerard D. McCarthy; Evin McGovern; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Plant extracts and compounds for combating schistosomiasis - Hesham R. El-Seedi; Shaden A. M. Khalifa; Azza H. Mohamed; Nermeen Yosri; Chao Zhao; Nabil El-Wakeil; Nour F. Attia; Baojun Xu; AbdElhafez R. AbdElhafez; Mohammad H. Boskabady; Sherif Elseedy; Thomas Efferth; et al. (Phytochemistry Reviews, 2023)
Schistosomiasis is a vector-borne water-based disease caused by Schistosoma blood flukes. It mostly affects people in low-income regions, 90% of reported cases being in developing countries. Schistosoma has a complex lifecycle, alternately infecting mammalian hosts and snails. The snails hosting the parasite are the most viable targets. Selective preparations for reducing the parasite pool in snails and infected water are required as current molluscicides are also nontoxic to other organisms, including fish, and thus affect food supplies in infected areas. Plants (e.g. Annona crassiflora Mart., A. muricata L., and A. montana Macfad.) are attractive potential sources as alternative molluscicides and novel entity to treat the disease owned to their diverse biologically potent compounds including; saponins, alkaloids, terpenoids, and tannins. Additionally, they can be locally cultivated, providing income for farmers and reducing treatment costs. Here, we review plants, plant extracts and isolated compounds that have shown activities against the host snails or Schistosoma in various parts of its life cycle. Plants have a lot of potential and will continue to contribute feasible, effective medicines and/or pesticides; more research is warranted to fully explore their future applications. Graphical abstract

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Acceptable intakes (AIs) for 11 small molecule N-nitrosamines (NAs) - Joel P. Bercu; Melisa Masuda-Herrera; Alejandra Trejo-Martin; Priyanka Sura; Robert Jolly; Michelle Kenyon; Rob Thomas; David J. Ponting; David Snodin; Gregor Tuschl; Stephanie Simon; Kathleen De Vlieger; et al. (Regulatory Toxicology and Pharmacology, 2023)

Factors influencing submerged macrophyte presence in fresh and brackish eutrophic waters and their impact on carbon emissions - Thomas Gremmen; Gijs van Dijk; Jaap Postma; Maite Colina; Lisette N. de Senerpont Domis; Mandy Velthuis; Rob van de Haterd; Fred Kuipers; Huibert van Rossum; Alfons J.P. Smolders; Sarian Kosten (Aquatic Botany, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

A CFD-based framework to assess airborne infection risk in buildings - Giulio Vita; Darren Woolf; Thomas Avery-Hickmott; Rob Rowsell (Building and Environment, 2023)

Protected areas support more species than unprotected areas in Great Britain, but lose them equally rapidly - Rob Cooke; Francesca Mancini; Robin J. Boyd; Karl L. Evans; Anna Shaw; Thomas J. Webb; Nick J.B. Isaac (Biological Conservation, 2023)

Abundance and seasonality of phoronid larvae in coastal temperate waters: More abundant than previously thought? - Maria McGuinness; Hannah Brownlow; Rob McAllen; Luke Harman; Damien Haberlin; Thomas K. Doyle (Aquatic Ecology, 2022)
In zooplankton surveys, many smaller taxa or species considered less important are often overlooked. One such example is the actinotrocha larvae of phoronid worms that are rarely quantified in zooplankton samples yet may play important roles in marine food webs. To gain a better understanding of phoronid ecology in coastal waters, we retrospectively analysed 145 plankton samples collected from two coastal sites in Ireland (Lough Hyne and Bantry Bay). Samples were collected using plankton nets from depths of 20 and 40 m. Phoronids were present in 37.7% and 38.2% of samples, with mean abundances of 0.3 ± 0.5 ind. m −3 and 1.2 ± 2.8 ind. m −3 , respectively, and were identified as Phoronis muelleri and Phoronis hippocrepia . Phoronids were present consistently each year from April to October at Lough Hyne and from February to October at Bantry Bay. Comparisons with other taxa in Lough Hyne show that abundances are similar to those of fish larvae (1.1 ± 1.8 ind. m −3 ) and echinoderm larvae (2.3 ± 4.4 ind. m −3 ). Examination of these samples from Irish waters suggests that phoronids are more abundant in temperate waters than previously reported.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Correction to: Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2022)

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Pharmacokinetics and pharmacodynamics of intranasal remimazolam—a randomized controlled clinical trial - Marija Pesic; Frank Schippers; Rob Saunders; Lyn Webster; Martin Donsbach; Thomas Stoehr (European Journal of Clinical Pharmacology, 2020)
Purpose Remimazolam is a novel and ultra-short-acting sedative currently developed for intravenous use in procedural sedation, general anesthesia, and ICU sedation. However, intravenous administration is not always appropriate, depending on the patient or setting. This study evaluated intranasal administration as a potential alternative route. Methods The study used a randomized, double-blind, 9 period cross-over design to compare the pharmacokinetics, pharmacodynamics, and safety of single intranasal doses of 10, 20, and 40 mg remimazolam (as powder or solution) with intranasal placebo and 4 mg intravenous remimazolam. Results Intranasal remimazolam powder had a consistent absolute bioavailability of approximately 50%; T max was 10 min; AUC and C max were dose-proportional. The higher doses of intranasal solution, however, resulted in decreasing bioavailability and loss of dose-proportionality in AUC and C max despite complete drug absorption due to partial swallowing of dose and the resulting first-pass effect. Pharmacodynamics were generally consistent with PK. Peak effects (drowsiness, relaxation, any, memory, response time) were in similar ranges after intranasal (10 to 40 mg) as intravenous (4 mg) dosing and were partially, but not consistently, dose-related. Safety results were generally consistent with other benzodiazepines; however, intranasal remimazolam (but not placebo) caused nasal discomfort/pain, in some cases even severe. Conclusions Intranasal administration of remimazolam was safe and caused sedative effects. However, the severe pain and discomfort caused by intranasal remimazolam prohibit its use by this route of administration, at least with the currently available intravenous formulation.

Eco-functionality of organic matter in soils - Ellis Hoffland; Thomas W. Kuyper; Rob N. J. Comans; Rachel E. Creamer (Plant and Soil, 2020)
Background Soil organic matter (SOM) supports multiple soil ecosystem functions, underpinned by processes such as C sequestration, N mineralization, aggregation, promotion of plant health and compound retention. We know little about the relationship between these functions and SOM quality. Scope We aimed to develop “eco-functionality” as a framework to address questions on the relation between SOM properties and soil ecosystem functions. Conclusions Paradigm shifts in SOM research have not led to metrics for eco-functionality beyond decomposability and C:N ratio. Recalcitrant OM is under-researched despite its essential role in aggregation and C sequestration, especially in C-saturated soils. Most soil functions are dependent on SOM decomposition and require labile compounds. We conclude that eco-functionality is context-dependent and needs to take time scales into account. We plea for attempts to link operationally defined SOM fractions to functions in order to make SOM research more applicable.

A modular approach to cataloguing marine science data - Adam Leadbetter; Will Meaney; Elizabeth Tray; Andrew Conway; Sarah Flynn; Tara Keena; Caoimhín Kelly; Rob Thomas (Earth Science Informatics, 2020)
The ability to access and search metadata for marine science data is both a key requirement for answering fundamental principles of data management (making data Findable, Accessible, Interoperable and Reusable) and also in meeting domain-specific, community defined standards and legislative requirements placed on data publishers. This paper describes a modular data model to answer the functional requirements developed from these drivers and illustrates how this data model can be operationalised. The ability of this solution to meet the FAIR principles is then assessed.

Implementation of a Data Management Quality Management Framework at the Marine Institute, Ireland - Adam Leadbetter; Ramona Carr; Sarah Flynn; Will Meaney; Siobhan Moran; Yvonne Bogan; Laura Brophy; Kieran Lyons; David Stokes; Rob Thomas (Earth Science Informatics, 2020)
The International Oceanographic Data and Information Exchange of UNESCO’s Intergovernmental Oceanographic Commission (IOC-IODE) released a quality management framework for its National Oceanographic Data Centre (NODC) network in 2013. This document is intended, amongst other goals, to provide a means of assistance for NODCs to establish organisational data management quality management systems. The IOC-IODE’s framework also promotes the accreditation of NODCs which have implemented a Data Management Quality Management Framework adhering to the guidelines laid out in the IOC-IODE’s framework. In its submission for IOCE-IODE accreditation, Ireland’s National Marine Data Centre (hosted by the Marine Institute) included a Data Management Quality Management model; a manual detailing this model and how it is implemented across the scientific and environmental data producing areas of the Marine Institute; and, at a more practical level, an implementation pack consisting of a number of templates to assist in the compilation of the documentation required by the model and the manual.

Distinct gelatinous zooplankton communities across a dynamic shelf sea - Damien Haberlin; Robin Raine; Rob McAllen; Thomas K. Doyle (Limnology and Oceanography, 2019)
Understanding how gelatinous zooplankton communities are structured by local hydrography and physical forcing has important implications for fisheries and higher trophic predators. Although a large body of research has described how fronts, hydrographic boundaries, and different water masses (e.g., mixed vs. stratified) influence phytoplankton and zooplankton communities, comparatively few studies have investigated their influence on gelatinous zooplankton communities. In July 2015, 49 plankton samples were collected from 50 m depth to the surface, across five transects in the Celtic Sea, of which, four crossed the Celtic Sea Front. Two distinct gelatinous communities were found in this dynamic shelf sea: a cold water community in the cooler mixed water that mainly contained neritic taxa and a warm water community in the warmer stratified water that contained a mixture of neritic and oceanic taxa. The gelatinous biomass was 40% greater in the warm water community (∼ 2 mg C m −3 ) compared with the cold water community (∼ 1.3 mg C m −3 ). The warm water community was dominated by Aglantha digitale, Lizzia blondina , and Nanomia bijuga , whereas the cold water community was dominated by Clytia hemisphaerica and ctenophores. Physonect siphonophores contributed > 36% to the gelatinous biomass in the warm water community, and their widespread distribution suggests they are ecologically more important than previously thought. A distinct oceanic influence was also recorded in the wider warm water zooplankton community, accounting for a ∼ 20 mg C m −3 increase in biomass in that region.

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Predicting the cumulative effect of multiple disturbances on seagrass connectivity - Alana Grech; Emmanuel Hanert; Len McKenzie; Michael Rasheed; Christopher Thomas; Samantha Tol; Mingzhu Wang; Michelle Waycott; Jolan Wolter; Rob Coles (Global Change Biology, 2018)
The rate of exchange, or connectivity, among populations effects their ability to recover after disturbance events. However, there is limited information on the extent to which populations are connected or how multiple disturbances affect connectivity, especially in coastal and marine ecosystems. We used network analysis and the outputs of a biophysical model to measure potential functional connectivity and predict the impact of multiple disturbances on seagrasses in the central Great Barrier Reef World Heritage Area (GBRWHA), Australia. The seagrass networks were densely connected, indicating that seagrasses are resilient to the random loss of meadows. Our analysis identified discrete meadows that are important sources of seagrass propagules and that serve as stepping stones connecting various different parts of the network. Several of these meadows were close to urban areas or ports and likely to be at risk from coastal development. Deep water meadows were highly connected to coastal meadows and may function as a refuge, but only for non‐foundation species. We evaluated changes to the structure and functioning of the seagrass networks when one or more discrete meadows were removed due to multiple disturbance events. The scale of disturbance required to disconnect the seagrass networks into two or more components was on average >245 km, about half the length of the metapopulation. The densely connected seagrass meadows of the central GBRWHA are not limited by the supply of propagules; therefore, management should focus on improving environmental conditions that support natural seagrass recruitment and recovery processes. Our study provides a new framework for assessing the impact of global change on the connectivity and persistence of coastal and marine ecosystems. Without this knowledge, management actions, including coastal restoration, may prove unnecessary and be unsuccessful.

Climate change vulnerability for species—Assessing the assessments - Christopher J. Wheatley; Colin M. Beale; Richard B. Bradbury; James W. Pearce‐Higgins; Rob Critchlow; Chris D. Thomas (Global Change Biology, 2017)
Climate change vulnerability assessments are commonly used to identify species at risk from global climate change, but the wide range of methodologies available makes it difficult for end users, such as conservation practitioners or policymakers, to decide which method to use as a basis for decision‐making. In this study, we evaluate whether different assessments consistently assign species to the same risk categories and whether any of the existing methodologies perform well at identifying climate‐threatened species. We compare the outputs of 12 climate change vulnerability assessment methodologies, using both real and simulated species, and validate the methods using historic data for British birds and butterflies (i.e. using historical data to assign risks and more recent data for validation). Our results show that the different vulnerability assessment methods are not consistent with one another; different risk categories are assigned for both the real and simulated sets of species. Validation of the different vulnerability assessments suggests that methods incorporating historic trend data into the assessment perform best at predicting distribution trends in subsequent time periods. This study demonstrates that climate change vulnerability assessments should not be used interchangeably due to the poor overall agreement between methods when considering the same species. The results of our validation provide more support for the use of trend‐based rather than purely trait‐based approaches, although further validation will be required as data become available.

A primer on systematic reviews in toxicology - Sebastian Hoffmann; Rob B. M. de Vries; Martin L. Stephens; Nancy B. Beck; Hubert A. A. M. Dirven; John R. Fowle; Julie E. Goodman; Thomas Hartung; Ian Kimber; Manoj M. Lalu; Kristina Thayer; Paul Whaley; et al. (Archives of Toxicology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Building strong relationships between conservation genetics and primary industry leads to mutually beneficial genomic advances - Stephanie J. Galla; Thomas R. Buckley; Rob Elshire; Marie L. Hale; Michael Knapp; John McCallum; Roger Moraga; Anna W. Santure; Phillip Wilcox; Tammy E. Steeves (Molecular Ecology, 2016)
Several reviews in the past decade have heralded the benefits of embracing high‐throughput sequencing technologies to inform conservation policy and the management of threatened species, but few have offered practical advice on how to expedite the transition from conservation genetics to conservation genomics. Here, we argue that an effective and efficient way to navigate this transition is to capitalize on emerging synergies between conservation genetics and primary industry (e.g., agriculture, fisheries, forestry and horticulture). Here, we demonstrate how building strong relationships between conservation geneticists and primary industry scientists is leading to mutually‐beneficial outcomes for both disciplines. Based on our collective experience as collaborative New Zealand‐based scientists, we also provide insight for forging these cross‐sector relationships.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

The Tosontsengel Mongolia world record sea‐level pressure extreme: spatial analysis of elevation bias in adjustment‐to‐sea‐level pressures - Gomboluudev Purevjav; Robert C. Balling; Randall S. Cerveny; Rob Allan; Gilbert P. Compo; Philip Jones; Thomas C. Peterson; Manola Brunet; Fatima Driouech; José Luis Stella; Bohumil M. Svoma; Daniel Krahenbuhl; et al. (International Journal of Climatology, 2015)
A World Meteorological Organization ( WMO ) committee evaluated the record sea‐level pressure ( SLP ) measurement of 1089.4 hPa on 30 December 2004 in Tosontsengel, Mongolia (1724.6 m). Although instrumentation and data collection procedures were properly followed according to the assessment of the committee, concern was raised regarding the reliability of SLP adjustment from such a high‐elevation station. This paper addresses this concern with a number of analyses that look at relationships between SLP extremes and corresponding station elevation and temperature. First, we selected data from stations extracted from the Integrated Surface Database ( ISD ‐Lite) of NOAA 's National Climate Data Center. A spatial analysis indicates that elevation shows little to no association ( R 2 values essentially zero) to extreme SLP . However, a second analysis between extreme SLP and air temperature indicates that high regionalism exists in spatial correlations (local R 2 ) between those two variables. This relationship to temperature is likely the result of differences in SLP adjustment formulae used around the world. Based on this analysis, on the need to differentiate the SLP values adjusted using extremely cold temperatures (and generally high elevation), and following past WMO SLP guidelines, the WMO Rapporteurs for Climate and Weather Extremes therefore have created two distinct SLP records: (a) highest adjusted SLP (below 750 m), currently 1083.3 hPa recorded on 31 December 1968 at Agata, Evenhiyskiy, Russia; and (b) highest adjusted SLP (above 750 m), currently 1089.4 hPa (by Russian method; 1089.1 hPa by WMO formula) on 30 December 2004 in Tosontsengel, Mongolia. Future WMO guidance regarding SLP adjustment may lead to re‐evaluation of this and other SLP records.

Deep geothermal: The ‘Moon Landing’ mission in the unconventional energy and minerals space - Klaus Regenauer-Lieb; Andrew Bunger; Hui Tong Chua; Arcady Dyskin; Florian Fusseis; Oliver Gaede; Rob Jeffrey; Ali Karrech; Thomas Kohl; Jie Liu; Vladimir Lyakhovsky; Elena Pasternak; et al. (Journal of Earth Science, 2015)

Toxicogenomics directory of chemically exposed human hepatocytes - Marianna Grinberg; Regina M. Stöber; Karolina Edlund; Eugen Rempel; Patricio Godoy; Raymond Reif; Agata Widera; Katrin Madjar; Wolfgang Schmidt-Heck; Rosemarie Marchan; Agapios Sachinidis; Dimitry Spitkovsky; et al. (Archives of Toxicology, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Land use impacts on biodiversity in LCA: a global approach - Laura de Baan; Rob Alkemade; Thomas Koellner (The International Journal of Life Cycle Assessment, 2013)

A tree-ring reconstruction of East Anglian (UK) hydroclimate variability over the last millennium - Richard J. Cooper; Thomas M. Melvin; Ian Tyers; Rob J. S. Wilson; Keith R. Briffa (Climate Dynamics, 2013)

Well characterized antihistamine 4 receptor antibodies contribute to current knowledge of the expression and biology of the human and murine histamine 4 receptor - Ralf Gutzmer; Thomas Werfel; Wolfgang Bäumer; Manfred Kietzmann; Paul L. Chazot; Rob Leurs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Large-scale sampling reveals the spatio-temporal distributions of the jellyfish Aurelia aurita and Cyanea capillata in the Irish Sea - Thomas Bastian; Damien Haberlin; Jennifer E. Purcell; Graeme C. Hays; John Davenport; Rob McAllen; Thomas K. Doyle (Marine Biology, 2011)

Prioritising biosecurity investment between agricultural and environmental systems - David C. Cook; Rob W. Fraser; Jeffrey K. Waage; Matthew B. Thomas (Journal of Consumer Protection and Food Safety, 2011)

Phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs were determined by geological processes and climate change in the Late Cenozoic - Çiğdem Akın; C. Can Bilgin; Peter Beerli; Rob Westaway; Torsten Ohst; Spartak N. Litvinchuk; Thomas Uzzell; Metin Bilgin; Hansjürg Hotz; Gaston‐Denis Guex; Jörg Plötner (Journal of Biogeography, 2010)
Aim Our aims were to assess the phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs and to estimate divergence times using different geological scenarios. We relate divergence times to past geological events and discuss the relevance of our data for the systematics of eastern Mediterranean water frogs. Location The eastern Mediterranean region. Methods Genetic diversity and divergence were calculated using sequences of two protein‐coding mitochondrial (mt) genes: ND2 (1038 bp, 119 sequences) and ND3 (340 bp, 612 sequences). Divergence times were estimated in a Bayesian framework under four geological scenarios representing alternative possible geological histories for the eastern Mediterranean. We then compared the different scenarios using Bayes factors and additional geological data. Results The extensive genetic diversity in mtDNA divides eastern Mediterranean water frogs into six main haplogroups (MHGs). Three MHGs were identified on the Anatolian mainland; the most widespread MHG with the highest diversity is distributed from western Anatolia to the northern shore of the Caspian Sea, and includes the type locality of Pelophylax ridibundus . The other two Anatolian MHGs are restricted to south‐eastern Turkey, occupying localities west and east of the Amanos mountain range. One of the remaining three MHGs is restricted to Cyprus; the second, to the Levant; and the third was found in the distribution area of European lake frogs ( P. ridibundus group), including the Balkans. Main conclusions Based on geological evidence and estimates of genetic divergence we hypothesize that the water frogs of Cyprus have been isolated from the Anatolian mainland populations since the end of the Messinian salinity crisis (MSC), that is, since c . 5.5–5.3 Ma, while our divergence time estimates indicate that the isolation of Crete from the mainland populations (Peloponnese, Anatolia) probably pre‐dates the MSC. The observed rates of divergence imply a time window of c. 1.6–1.1 million years for diversification of the largest Anatolian MHG; divergence between the two other Anatolian MHGs may have begun about 3.0 Ma, apparently as a result of the uplift of the Amanos Mountains. Our mtDNA data suggest that the Anatolian water frogs and frogs from Cyprus represent several undescribed species.

Differential induction of apoptosis and inhibition of the PI3-kinase pathway by saturated, monounsaturated and polyunsaturated fatty acids in a colon cancer cell model - Anna-Mart Engelbrecht; Joe-Lin du Toit-Kohn; Beverly Ellis; Mark Thomas; Theo Nell; Rob Smith (Apoptosis, 2008)

Development of EST-microsatellites from the cycad Cycas rumphii, and their use in the recently endangered Cycas micronesica - Angélica Cibrián-Jaramillo; Thomas E. Marler; Rob DeSalle; Eric D. Brenner (Conservation Genetics, 2008)

Whole season net community production in the Weddell Sea - Mario Hoppema; Rob Middag; Hein J. W. de Baar; Eberhard Fahrbach; Evaline M. van Weerlee; Helmuth Thomas (Polar Biology, 2007)

Population structure and mitochondrial DNA variation in sedentary Neotropical birds isolated by forest fragmentation - Laura M. Brown; Rob R. Ramey; Beth Tamburini; Thomas A. Gavin (Conservation Genetics, 2004)

Interleukin-10 promoter polymorphisms and the outcome of hepatitis C virus infection - Susanne Knapp; Branwen J. W. Hennig; Angela J. Frodsham; Lyna Zhang; Simon Hellier; Mark Wright; Rob Goldin; Adrian V. S. Hill; Howard C. Thomas; Mark R. Thursz (Immunogenetics, 2003)

Molecular cytogenetic analysis of a novel high-grade canine T-lymphoblastic lymphoma demonstrating co-expression of CD3 and CD79a cell markers - Rachael Thomas; Ken C. Smith; Rob Gould; Sue M. Gower; Matthew M. Binns; Matthew Breen (Chromosome Research, 2001)

What Is a Good Public Participation Process? Five Perspectives from the Public - ROB KRUEGER; SETH TULER; THOMAS WEBLER (Environmental Management, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Conservation and Civil Strife: Two Perspectives from Central Africa - Terese Hart; John Hart; Cheryl Fimbel; Robert Fimbel; William F. Laurance; Carrie Oren; Thomas T. Struhsaker; Howard C. Rosenbaum; Peter D. Walsh; Yvette Razafindrakoto; Michel Vely; Rob DeSalle (Conservation Biology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Physiologically based pharmacokinetic/pharmacodynamic modeling of the toxicologic interaction between carbon tetrachloride and Kepone - H. A. El-Masri; Russell S. Thomas; G. Rob Sabados; Jenny K. Phillips; Alexander A. Constan; Stephen A. Benjamin; Melvin E. Andersen; Harihara M. Mehendale; Raymond S. H. Yang (Archives of Toxicology, 1996)